2015
DOI: 10.5603/kp.a2015.0098
|View full text |Cite
|
Sign up to set email alerts
|

Relation of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratio with coronary artery disease severity in patients undergoing coronary angiography

Abstract: A b s t r a c tBackground: Atherosclerosis is a chronic systemic inflammatory disease. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are systemic inflammatory markers that are correlated with poor cardiovascular outcomes. Aim:To explore the relation of NLR and PLR with severity of coronary artery disease (CAD). Methods:The study population consisted of 180 consecutive patients who underwent elective coronary angiography (CAG). While 100 patients (22 female, mean age: 60.6 ± 12.6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 24 publications
2
61
0
3
Order By: Relevance
“…PLR is also known as a good prognostic marker for cardiovascular events 21)22). In a previous study, combined NLR and PLR levels also predicted severity of CAD23) and adverse clinical outcomes 24). In our study, PLR was also a good predictor for all-cause death during 24 months of follow-up, and the AUC of PLR was similar to that of combined NLR and CRP.…”
Section: Discussionsupporting
confidence: 77%
“…PLR is also known as a good prognostic marker for cardiovascular events 21)22). In a previous study, combined NLR and PLR levels also predicted severity of CAD23) and adverse clinical outcomes 24). In our study, PLR was also a good predictor for all-cause death during 24 months of follow-up, and the AUC of PLR was similar to that of combined NLR and CRP.…”
Section: Discussionsupporting
confidence: 77%
“…Acar et al20) demonstrated that high PLR is related with coronary collateral development in patients with chronic total occlusions. Sarı et al21) revealed that pre-procedural PLR is associated with coronary atherosclerosis severity.…”
Section: Discussionmentioning
confidence: 99%
“…PLR is calculated from systemic inflammatory markers as a predictor of poor cardiovascular outcomes [11]. Recent studies have demonstrated that the PLR is associated with MACE and that it is an independent marker of mortality in some oncological and cardiac diseases [12,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets play a key role in the pathophysiology of ACS. Higher levels of inflammatory markers are associated with the severity of coronary artery disease (CAD) and worse cardiovascular outcome [11]. e platelet-lymphocyte ratio (PLR), which is calculated by the division of absolute platelet count by absolute lymphocyte count, has been stated to be a new indicator of inflammatory response.…”
Section: Introductionmentioning
confidence: 99%